The new landscape of collaboration - Shane Coen (Oz, 2010)
When I began my practice in 1992 with my former partner, Jon Stumpf, we set out by establishing a small set of core goals for our firm. The heart of these was to promote design excellence and to collaborate with the world’s greatest thinkers in the architectural and design community.